Analysis of uveitis rates across all etanercept ankylosing spondylitis clinical trials. Issue 01 (21st May 2009) - Sieper, J; Koenig, A; Baumgartner, S; Wishneski, C; Foehl, J; Vlahos, B; Freundlich, B
Abstract : Objective: To assess uveitis (including iritis and iridocyclitis) incidence from clinical trials of etanercept in patients with ankylosing spondylitis (AS). Methods: Clinical trials of etanercept in AS (four placebo-controlled; one active-controlled; three open-label) were examined for reports of uveitis. Between-group differences with confidence intervals (CIs) in the uveitis rates were calculated for the double-blind, active-controlled and long-term studies. Results: In placebo-controlled trials, the uveitis rate per 100 subject years (95% CI) for etanercept (8.6 (4.5 to 14.2)) was lower than that for placebo (19.3 (11.0 to 29.8), p = 0.03). In the active comparator trial, rates for etanercept and sulfasalazine were similar (10.7 (5.5 to 17.6) and 14.7 (6.4 to 26.5), respectively; p = 0.49). The long-term rate for etanercept, estimated from both placebo-controlled and open-label extension studies was 12.0 (10.0 to 14.1). Conclusions: In subjects with AS, rates of uveitis events with etanercept were lower than with placebo in placebo-controlled trials and similar to sulfasalazine in an active comparator trial.